ICU care of abdominal organ transplant patients - Al-Khafaji, Ali ([New York] : Oxford University Press, 2013)
Pre- and post-operative care of transplant patients is an aspect of critical care medicine in which most ICU physicians and nurses have received little or no formal training and are left to cope with this complex population with only spotty incomplete'on-the-job experience' as a guide. In response to this clinical knowledge gap, this book provides a concise'at the bedside' resource for clinicians caring for abdominal organ transplant patients before and after surgery.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Aug 12, 2013).
Keywords: Liver -- Transplantation; Critical care medicine; Kidneys -- Transplantation; Pancreas -- Transplantation